Samuel Rutherford – the monarchy of law or the monarchy of saints? - Tulejski, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2020)
Samuel Rutherford – Scottish Presbyterian priest and political thinker who lived in the times of English civil war – is commonly considered as one of the theorists of the monarchy of law concept, the mixed constitution and the right of revolution. All these ideas are fundamental for modern English constitutionalism which is in opposition to the idea of monarchical absolutism which is based on the concept of the social contract. For this reason, he was among the authorities quoted by the Founding Fathers during their opposition against the arbitrary powers of the Metropole. Meanwhile, the global analysis of his achievements put in doubts many circulating opinions regarding the author of Lex, Rex. In this article, an author proves that the hermeneutic analysis of Rutherford’s political theology suggests that Rutherford was not the theorist of the monarchy of law in its common meaning, but rather theonomic vision of the state.